Effect of Potassium Fertilization on Lettuce´ s (Lactuca sativa L.) under Different Sodium Media - UCAR, YUSUF; KADAYIFCI, ABDULLAH; ERDAL, IBRAHIM; I. TUYLU, GOKHAN; SENYIGIT, ULAS (Asian Journal of Chemistry, 2010)
The aim of this study was to determine the effect of potassium fertilization on the yield parameters and evapotranspiration of lettuce (Lactuca sativa L.) on the growing media contained different Na+/K+ rate. The study was carried out as pot experiments with three replicate under the greenhouse conditions. The growing media was constituted of perlit deprived on chemicals. At the beginning of the experiment, nutrients necessary for growing of the plants were applied to the media in order to obtain the optimum growing conditions in all treatments. Four different growing media were constituted of Na+/K+ rates with 0, 0.5, 1.0 and 2.0 value and the K+ fertilization was applied as 10, 30, 50 and 70 mg kg-1, respectively. During experiment, irrigation water was applied to prevent yield diminishing caused by water deficit and evapotranspiration were calculated by water budget equation. Based on the results, there were found statistical significant differences at p ≤ 0.01 confidence level throughout yields, lengths and surface diameters of lettuce (Lactuca sativa L.). For experiment conditions, lettuce's yields were decreased in significant level by increasing of Na contents in growing media. Therefore, fertilization especially in the level of K3 and K4 increased the yield in significant level in the growing media contained high rate of Na+. On the other hand, K+ fertilization was determined to tolerate Na+ dosage. Although statistical significant difference were found at p ≤ 0.01 confidence level in water consumption between treatments, there was statistical insignificant relation between Na+ content and evapotranspiration. On the other hand, evapotranspiration was not influenced by excess Na+ in growing media. Because, growing media were constituted from perlit and its structure was not spoiled by Na+ effect as soil.